CDMA Time-hopping optical network with enhanced security - Ortega, A. A. (2012)
A method to provide cryptographically secure point-to-point and point-to-multipoint communication using an encrypted Bloom filter is implemented on a time-hopping CDMA optical fiber network. A novel Hammingweight minimization coding algorithm optimises the performance of the encrypted Bloom filter in terms of end-user bandwidth utilisation over previous proposals. The system has a total channel utilisation of up to 29% for 128 simultaneous users, up to 20 km apart, served by a single passive optical hub, or longer distances if served by an active hub.